PENGEMBANGAN MEDIA LITERASILIWANGI BERBASIS APLIKASI PODCAST MENUJU MAHASISWA DENGAN LITERASI UNGGUL - Iis Siti Salamah Azzahra; Qudratullah (Jurnal Semantik, 2024)
A good level of literacy is the basis for educational progress, apart from having the ability to absorb information, students must also be able to produce content and information as part of literacy and is not limited to writing, but also includes audio or podcast-based content. This creation process must be supported by a platform that can become a forum for creativity and foster a spirit of literacy. This research aims to provide an overview of the development of podcast media that students can use to improve literacy activities. The research method used is RnD (Reasearch and Development). Data collection techniques using documentation, observation sheets, questionnaires, product validation and tests. The place of this research is at IKIP Siliwangi.  The results of media validation for language learning show a percentage of 95.69% of all experts and practitioners. The output of this research is a web application based on gamified broadcasts which makes literacy activities in the tertiary environment more interesting, trains students to be able to use technological devices and provides a new space for students to improve their literacy skills through audio content and these conditions are the basis for achieving high literacy excel among students.